2019
DOI: 10.21608/ejentas.2019.12297.1106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life after Functional Endoscopic Sinus Surgery (FESS) in chronic rhinosinusitis patients in Menoufia Governorate

Abstract: Background: Chronic rhinosinusitis has a great impact on the quality of life. Functional endoscopic sinus surgery is the treatment of choice for chronic rhinosinusitis refractory to medical treatment as it allows restoring ventilation and mucociliary clearance. Sino-Nasal Outcome Test 22 questionnaire has been used for evaluating changes in symptoms and predicting the extent of postoperative outcome. Objective: The aim of the study was to evaluate how functional endoscopic sinus surgery affects the outcome in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…These results agreed with Qadeer et al (2018) (8) who studied about "Quality of Life after Functional Endoscopic Sinus Surgery in Patients with Chronic Rhinosinusitis" and reported that more than two fifth diagnosed CRSwNP. Similar to Behiry etal (2019) (20) , who studied "Evaluation of quality of life after Functional Endoscopic Sinus Surgery (FESS) in chronic rhinosinusitis patients in Menoufia Governorate." The study showed that CRSwNP among two third s of the sample.…”
Section: Discussionmentioning
confidence: 89%
“…These results agreed with Qadeer et al (2018) (8) who studied about "Quality of Life after Functional Endoscopic Sinus Surgery in Patients with Chronic Rhinosinusitis" and reported that more than two fifth diagnosed CRSwNP. Similar to Behiry etal (2019) (20) , who studied "Evaluation of quality of life after Functional Endoscopic Sinus Surgery (FESS) in chronic rhinosinusitis patients in Menoufia Governorate." The study showed that CRSwNP among two third s of the sample.…”
Section: Discussionmentioning
confidence: 89%
“…Primarily, with FESS, the disease-specific QOL can be significantly improved. Three separate studies demonstrate this finding in Egypt by Behiry et al [ 15 ], Iran by Aghdas et al [ 16 ], and Morocco by Laababsi et al [ 17 ]. A significant improvement has been observed in the QOL scores between preoperative and postoperative observations [ 17 ].…”
Section: Reviewmentioning
confidence: 93%
“…Therefore, patients with CRS often complain of excessive sleepiness and fatigue during the day. Since CRS affects the local area and the body as a whole, and FESS reduces the burden of the disease by improving systemic cytokine levels, it is reasonable to assume that FESS would also lead to improved sleep outcomes [ 15 ]. These symptom improvements inform the overall QOL of the patients under treatment.…”
Section: Reviewmentioning
confidence: 99%